Вплив рециркуляції відпрацьованих газів на показники сучасного бензинового двигуна з відключенням групи циліндрів - Гутаревич, Юрій Феодосійович; Карев, С. В. (НТУ "ХПІ", 2015)
В даній статті наведені результати експериментальних досліджень по впливу рециркуляції відпрацьованих газів, з відбором після нейтралізатора, на показники сучасного бензинового двигуна з відключенням групи циліндрів. Представлено методику визначення коефіцієнта рециркуляції відпрацьованих газів, виходячи з балансу теплоти. Визначений оптимальний коефіцієнт рециркуляції відпрацьованих газів для двигуна 6Ч 9,5/6,98 для режиму, який широко використовується в умовах експлуатації.

In the article presents the results of experimental studies on the effects of recirculation of exhaust gases, with pick exhaust gases after neutralizing tank, the performance of modern gasoline engine with disconnected cylinders. The method of determining the coefficient of exhaust gas recirculation, based on heat balance. The results of experimental studies have shown that using of exhaust gas recirculation in modern gasoline engine did not influence on ratio of the fuel–air mixture results, decreased the fuel consumption per hour, and therefore effective power, sharply decreased the concentration of nitrogen oxides, the concentration of oxide and dioxide carbon almost not changed, the concentration of hydrocarbons slightly increased. Featuring the derivative of nitrogen oxides and specific fuel consumption have determined optimal ratio of exhaust gas recirculation for 6CH 9.5/6.98 engine for the mode, which is widely used in operation, according to the profile it is 6 ... 6.5%.
Influence of exhaust gas recirculationon the performance of modern gasoline engine with group of cylinders which disconnected
Keywords: регулювання потужності; оксиди азоту; РВГ; КМРП; exhaust gas recirculation; petrol engine; nitrogen oxides